Pengembangan Program Pendidikan Islam Berbasis Teknologi Informasi - Sugianto; Ahmad Subagyo; Muhammad Sofian Hadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of an Islamic education program based on information technology is a response to the challenges of the digital era that demands a more adaptive and innovative transformation of the learning system. Islamic education as an integral part of the national education system has an urgency to adopt information technology in order to be able to provide relevant and competitive education services in the era of the Industrial Revolution 4.0. This study aims to examine the strategy, implementation, and impact of information technology integration in the development of Islamic education programs. The research method used is a qualitative approach with literature studies and observations of good practices in several Islamic education units. Data were collected through documentation and review of national education policies related to the digitalization of education. The analysis was carried out descriptively-analystically to understand the integration patterns and challenges faced in the development of IT-based Islamic education programs. The results of the study show that the use of the Learning Management System (LMS), digital learning applications, and web-based interactive media has increased student engagement in learning and strengthened the achievement of spiritual, social, and academic competencies. The development of Islamic content in multimedia format also enriches the learning experience of students in a contextual and enjoyable way. However, several challenges are still encountered, such as limited digital infrastructure, educator competence in utilizing IT, and resistance to changes in traditional teaching methods. To overcome this, supporting policies, ongoing training for teachers, and strengthening collaboration between technology developers, educational institutions, and other stakeholders are needed. Thus, the development of information technology-based Islamic education programs must be designed systematically by considering pedagogical, technological, and Islamic values. This development model is expected to be a reference in building an inclusive, dynamic, and future-oriented Islamic education ecosystem.